Chronic Hepatitis E Infection Resulting in Graft Failure in a Liver Transplant Tourist. (2nd July 2011) - Tan, Hui-Hui; Leong, Hoe-Nam; Tan, Boon-Huan; Oon, Lynette Lin-Ean; Lim, Kiat-Hon; Chang, Jason Pik-Eu; Tan, Chee-Kiat
Abstract : Hepatitis E, usually an acute hepatitis in the immunocompetent, has a chronic form described in immunocompromised hosts. We report the clinical course and outcome of an adult liver transplant recipient whose posttransplant period was complicated by chronic hepatitis E, Epstein-Barr virus infection, and cellular rejection of the graft.